(untitled) (Encuentros, 2021)
This article presents the results of a qualitative investigation carried out on ten women presidents of the Community Action Boards (JAC) of Tunja, Colombia, in order to understand the leadership exercised in their administration. For this, were used a documentary analysis and a semi-structured interview, in which were studied three dimensions: leadership, family and government. It found the existence of obstacles from society and the communities they serve, as well as pressure from the family, which makes it difficult for them to carry out this work and pushes them not to be reelected in these positions.